2015
DOI: 10.5935/abc.20150124
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Electrocardiographic T-peak to T-end Interval in Subjects with Increased Epicardial Fat Tissue Thickness

Abstract: BackgroundThe association between periatrial adiposity and atrial arrhythmias has been shown in previous studies. However, there are not enough available data on the association between epicardial fat tissue (EFT) thickness and parameters of ventricular repolarization. Thus, we aimed to evaluate the association of EFT thickness with indices of ventricular repolarization by using T-peak to T-end (Tp-e) interval and Tp-e/QT ratio.MethodsThe present study included 50 patients whose EFT thickness ≥ 9 mm (group 1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“… 28 , 29 Recently, some myocardial repolarization markers, such as Tp-e interval, Tp-e/QT, and Tp-e/QTc ratios, have been reported to be useful in predicting lethal ventricular arrhythmias in various clinical disorders without structural heart disease. 7 , 30 , 31 Tp-e interval is considered a new marker of increased risk of SCD. Yamaguchi et al.…”
Section: Discussionmentioning
confidence: 99%
“… 28 , 29 Recently, some myocardial repolarization markers, such as Tp-e interval, Tp-e/QT, and Tp-e/QTc ratios, have been reported to be useful in predicting lethal ventricular arrhythmias in various clinical disorders without structural heart disease. 7 , 30 , 31 Tp-e interval is considered a new marker of increased risk of SCD. Yamaguchi et al.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown an association between EAT thickness and the presence and extent of CAD [4]. Furthermore, the myocardial ischemia-related ventricular repolarization parameters Tp-e and Tp-e/QT are also increased in patients with thicker EAT [11]. A study by Park et al that evaluated the association between EAT thickness and plaque structure using virtual histology intravascular ultrasound (VH-IVUS) revealed that thin-cap fibroatheromas (TCFAs) and higher necrotic core burden are associated with EAT thickness [12].…”
Section: Discussionmentioning
confidence: 99%
“…They demonstrated some ventricular repolarization abnormalities on electrocardiography in patients with higher EFT thickness. We would like to thank Kaplan et al 1 for their great effort in this study, and share some of our thoughts.…”
mentioning
confidence: 93%
“…It was with great interest that we read the paper by Kaplan et al 1 entitled ''Evaluation of Electrocardiographic T-peak to T-end Interval in Subjects with Increased Epicardial Fat Tissue Thickness'' published on Arquivos Brasileiros de Cardiologia in December 2015. They aimed to investigate the relationship between epicardial adipose tissue (EFT) and ventricular repolarization.…”
mentioning
confidence: 99%
See 1 more Smart Citation